ABSORPTION OF ARSENIC FOLLOWING INTRA-MUSCULAR INJECTIONS OF SALVARSAN AND NEOSALVARSAN - Swift, Homer F. (The Rockefeller University Press, 1913)
Intramuscular injection of salvarsan and neosalvarsan in rabbits always produces necrosis of the muscles. A much more intense reaction is produced by salvarsan than by neosalvarsan. The rate of absorption of arsenic following intramuscular injections of salvarsan is very slow, while following intramuscular injections of neosalvarsan between 75 and 85 per cent of the arsenic is absorbed during the first week. The subsequent absorption is quite slow.